Impact of Project Management Methodologies on IT Software Project Outcomes - Tkachev, Arseniy; Svatá, Vlasta, 1952-; Zbořil, Martin; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
This thesis investigates the impact of project management methodologies on Information Technology (IT) software development project outcomes, focusing on Traditional Project Management (TPM) and Agile Project Management (APM) approaches. The motivation is to understand how these methodologies influence success metrics such as time, cost, quality, stakeholder satisfaction, and business value across various IT projects. The study involves two practical case studies: a Sales Analyzer Application, a software development project that employs Waterfall methodology, and a Serialization project employing Agile. The analysis investigates how each methodology addresses project constraints, requirements, and objectives. The ultimate goal is to identify conditions where specific approaches perform exceptionally well. The case studies present insights from observing the project execution and success metrics.
Vedoucí práce: Vlasta Svatá
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses